THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES (Economic and Bussiness Faculty, Dr Soetomo University, 2016)
Abstract.This aims to determine the factors that affect the performance of employees of the University PGRI RonggolaweTuban. These factors are motivation and work environment. Employees who have a high motivation to work will have a positive impact for the organization, so as to achieve organizational goals. Hypothesis testing is done by spreading the questionnaire as many as 52 employees of the University PGRI RonggolaweTuban. Analysis using multiple linear regression analysis. Results of testing the hypothesis that the value F = 4,312; and p = 0.019 (p <0.05) that there is influence motivation and work environment on employee performance PGRI University RonggolaweTuban. The results of the partial test (t test) on the motivation variable, obtained t = 0.136, p = 0.892 (p> 0.05), meaning that work motivation has no significant effect on employee performance. On the environment variable obtained value t = 2,376; and p = 0.021 (p <0.05), which means that the working environment have a significant effect on employee performance. R2 = 0.115 shows that simultaneously motivated and able to contribute to the environmental performance of 11.5% on the employees of the University of PGRI RonggolaweTuban..